Protection of Consumer Rights on Unlabeled Food Products - Teddy Prima Anggriawan; Anajeng Esri Edhi Mahanani; Retno Mumpuni; Alvian Dwianngga Wijaya (Nusantara Science and Technology Proceedings, 2021)
Need the main human beings to include clothing, food, and shelter. In today's era, it is often seen that domestic industries or micro, small and medium enterprises are growing rapidly because in the current era they are supported by technological advances. One of the products is snacks. Most of these products are not included. expired the type of method used in this research is normative juridical. The research specification used by the author in this legal research is descriptive analysis. It is descriptive that this research was conducted by painting the object of research. In the UUPK it appears that good faith is more emphasized on business actors including home industry business actors because it covers all stages in carrying out their business activities so that it can be interpreted that the obligation of business actors to have good intentions starts from the time the goods are designed or produced until the after-sales stage. on the other hand, consumers are only required to have good intentions in making purchases of goods and/or services. This is of course caused by the possibility of harming consumers starting when the goods are designed or produced by producers or business actors, while for consumers the possibility of harming producers begins when they make transactions with producers.